1993
DOI: 10.1007/bf00233415
|View full text |Cite
|
Sign up to set email alerts
|

Microspore culture of Hordeum vulgare L.: the influence of density and osmolality

Abstract: Donor plants of Hordeum vulgare L. cv. Igri were grown in a conditioned environment to minimise fluctuations in the composition of the microspore population. After isolation different types of microspores were identified within each population, amongst others an embryogenic subpopulation. It was shown that the optimum plating density is achieved by adjusting the density to 2×10(4) embryogenic microspores per ml, with a lower threshold at 5×10(3) per ml. By increasing the osmolality of the pretreatment solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 18 publications
2
42
0
1
Order By: Relevance
“…The regenerated plants were completely fertile doubled haploids (Hoekstra et al, 1992;1993;Hu and Kasha, 1999). The high frequency of completely fertile plants indicates that chromosome doubling must occur very early, most likely at the time of induction (Kasha et al, 2001;Seguí-Simarro and Nuez, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The regenerated plants were completely fertile doubled haploids (Hoekstra et al, 1992;1993;Hu and Kasha, 1999). The high frequency of completely fertile plants indicates that chromosome doubling must occur very early, most likely at the time of induction (Kasha et al, 2001;Seguí-Simarro and Nuez, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mean viability of rye microspores after isolation from the analyzed populations from Danko was 87.6%, while for microspores from rye populations obtained from Poznań was 87.2%. Hoekstra et al (1993) characterized different types of barley microspores on the first days of culture. They showed that only microspores with a markedly enlarged diameter divide after a 3-day incubation in a medium that induces androgenesis.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to observe that while part of the microspores have adopted the sporophytic route the majority of them have degenerated. According to Hoekstra et al (1993), only 25% of the viable, potentially embryogenic microspores effectively divide themselves when cultured in vitro. Not all of these proceed their sporophytic development.…”
Section: Resultsmentioning
confidence: 99%